Transformational Leadership in the City of Yogyakarta During Herry Zudianto’s Era - ZUHRIYATI, ERNI; RAHMAWATI, DIAN EKA (Jurnal Studi Pemerintahan, 2014)
Political and governmental transformation that tookplace after the 1998 reformation brought the necessityfor the bureaucracy to make self improvement.Bureaucratic performance in providing public servicesbecame the main focus. In this framework, leadershipis the significant factor in performing a seriesof government innovation. This study aims to describethe implementation of transformational leadershipto create an innovative government inYogyakarta during Herry Zudianto’s Era. The categoryof this study is a qualitative research. The dataused is primary data that was obtained by interview,questionnaire, and observation, and secondary dataobtained with the technique of data collection documentation.The results showed that Herry Zudiantohas the criteria of transformative leadership in doinggovernment innovation with characteristics ofthe four dimensions, namely idealized influence, inspirationalmotivation, intellectual stimulation andindividualized consideration. Transformational leadershipby contextual style according to the demandsof the contemporary socio-politics has implicationsfor the occurrence of a change of two organizationalentities, namely organizational culture andinnovation in policy implementation.Keywords: transformational leadership,government’s innovation, governments ofYogyakarta